Reclamation of Bauxite Waste through Afforestation - Lal, Shyam (Indian Forester, 1991)
This paper presents an experiment conducted to reclaim the red mud an inevitable waste of Bauxite ore emerged by Hindalco by planting suitable species for improvement of ecological and environmental condition of the area.